2012
DOI: 10.1590/s0101-20612012005000019
|View full text |Cite
|
Sign up to set email alerts
|

Histochemistry and morphoanatomy study on guava fruit during ripening

Abstract: Guava (Psidium guajava L.) is a highly perishable fruit due to its intense metabolism during ripening. Information on the enzyme activities that degrade pectic substances, as well as the amount of pectin, is very contradictory and not clearly defined. Thus, this study aimed to monitor the changes occurred in the fruit during ripening through histochemical, physical, and scanning microscopy processes. Guavas were picked at the half-mature stage and stored for 9 days at 22 ± 1 °C and 78 ± 1% RH. The analyses con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
1
10
0
4
Order By: Relevance
“…The results of this study are similar to those reported by Botelho et al (2016) and Abreu et al (2012a), who reported a reduction of 70 and 73%, respectively, in the firmness of guava cv. Pedro Sato, during four days of storage at room temperature.…”
Section: Firmness and Phenolic Compoundssupporting
confidence: 92%
See 3 more Smart Citations
“…The results of this study are similar to those reported by Botelho et al (2016) and Abreu et al (2012a), who reported a reduction of 70 and 73%, respectively, in the firmness of guava cv. Pedro Sato, during four days of storage at room temperature.…”
Section: Firmness and Phenolic Compoundssupporting
confidence: 92%
“…Pectin polymers are considered primarily responsible for the firmness of green fruits (Abreu et al, 2012a) and their degradation is one of the most notable events during ripening and softening of the fruit. In guavas, it is not different.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outros açúcares neutros, como galactose e arabinose podem ser observados em cadeias laterais (FERNNDES et al, 2014). Vários são os usos da pectina, nos frutos os polímeros de pectina são os responsáveis por manter a firmeza dos frutos verde e maduros (SPILLER et al, 2018;ABREU et al, 2012), e nos processos industriais como por exemplo, pode ser utilizada na produção de minibactérias, na fabricação de gomas e balas de mascar, geleias, biofilmes e espessantes para sucos (LIMA et al, 2017;DA SILVA et al, 2014).…”
Section: ____________________________________________________________unclassified